Microlepidogaster dimorpha, a new species of Hypoptopomatinae (Siluriformes: Loricariidae) from the upper rio Paraná system - Martins,Fernanda de Oliveira (2011)
Microlepidogaster dimorpha, new species, is described from tributaries of rio Grande, upper rio Paraná system. Microlepidogaster dimorpha differs from M. perforatus and M. longicolla by having first dorsal-fin proximal radial attached to the neural spine of seventh vertebra, with posterior portion contacting also the eighth centrum (vs. first dorsal-fin proximal radial attached to the neural spine of eighth or ninth vertebra in M. perforatus, and to the neural spine of tenth or eleventh vertebra in M. longicolla); 29-30 vertebrae (vs. 31 in M. perforatus and 31-33 in M. longicolla); 18-21 mid-dorsal plates (vs. 9-13 in M. perforatus, and 13-17 in M. longicolla); deeper caudal peduncle (10.0-11.4% in SL vs. 7.7-8.5% in M. perforatus, and 5.4-7.3% in M. longicolla); greater distance between dorsal-fin origin and anal-fin insertion (19.4-23.8% in SL vs. 16.4-18.8% in M. perforatus, and 14.7-16.2% in M. longicolla); and nostril width markedly wider in males than in females (vs. approximately equivalent in size for both sexes, slightly wider in males than in females in M. perforatus, and equivalent in size for both sexes in M. longicolla). Microlepidogaster dimorpha also differs from M. perforatus by presence of the iris operculum (vs. absence); median plate series complete to caudal peduncle end (vs. median plate series truncated, with last two plates of dorsal and ventral series contacting in midline); greater head depth (43.4-53.1% vs. 40.7-42.3% in HL); greater orbital diameter (13.6-18.5% vs. 11.1-13.5% in HL); pelvic-fin first unbranched ray longer in males than in females (vs. equivalent in size in both sexes); and supraneural without paired anterior processes (vs. processes present). Additionally, M. dimorpha can be distinguished from M. longicolla by having anterior margin of snout with a paired rostral plate (vs. snout with small plates, naked in the anterior margin); by pectoral-fin axillary slit present, even in adult specimens (vs. pectoral-fin axillary slit present only in juvenile specimens); longer pectoral-fin unbranched ray (20.0-23.8% vs. 13.4-16.2% in SL in M. longicolla).